How Limiting Deceptive Practices Harms Consumers - Salvatore Piccolo; Piero Tedeschi; Giovanni Ursino (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2015)
There are two competing sellers of an experience good, one offers high quality, one low. The low-quality seller can engage in deceptive advertising, potentially fooling a buyer into thinking the product is better than it is. Although deceptive advertising might seem to harm the buyer, we show that he could be better off when the low-quality seller can engage in deceptive advertising than not. We characterize the optimal deterrence rule that a regulatory agency seeking to punish deceptive practices should adopt. We show that greater protection against deceptive practices does not necessarily improve the buyer-welfare.
Keywords: L13; L15; L4; 330; Misleading Advertising; Deception; Bayesian Consumers; Asymmetric Information